Dime Con Quién Anda Guadalupe - Warner, Michael (Lumen et Vita, 2023)
Dime con quién andas, y te diré quién eres – Tell me with whom you walk, and I will tell you who you are. This is one of the most common sayings in the Spanish language, and one that appears at least as far back as Cervantes’ Don Quijote de la Mancha, published in 1615. In this paper I will explore briefly how this saying applies to Our Lady of Guadalupe by asking with whom the Virgin walks in order to discern who the Virgin is. I consciously do not start with theology, with the magisterium, or with the clergy. Instead, I look at the story, and at the storytellers – those stories that describe mysteries “cured in centuries of blood and candle smoke,” those people for whom “five hundred years of sorrow have not destroyed their deepest faith.” In their experience and praxis we find Guadalupe.